As vozes que ninguém escuta: mulheres no sistema prisional brasileiro - Bedê, Nicole Ristow (2023)
The study argues that the lack of respect for the physical and moral integrity of prisoners is a responsibility of the state, which must provide environments suited to gender needs and individual conditions. Penitentiary law is a shared competence between the Union, the States and the Federal District, as legally determined by the 1988 Federal Constitution, in line with the principle of human dignity. In addition, the need for the effective application of human rights to women within the Brazilian prison system is highlighted, with a view to combating not only criminal violence, but also social, political, health and education exclusion. The importance of recognizing that the lack of gender distinction within female incarceration guarantees these inmates double punishment for their crimes, setting back any intention of re-socialization and reaffirming the patriarchal culture of our society. It can be understood that this crime against women occurs simply because they are women, without distinction of race, social class, religion or age, in both public and private spaces, maintaining the cycle of inferiorization of women in society. In this way, the text emphasizes the responsibility of the state to curb such actions, through direct and efficient public policies to minimize such damage, in order to promote a fairer and more equal society, especially in women's prisons.